Helicobacter pylori infection in asymptomatic rural Bangladeshi population - Rhaman, Mir Masudur; Rahman, Fahmida; Mazumder, Sraboni; Sayeed, M Abu; Haq, Jalaluddin Ashraful (IMC Journal of Medical Science, 2021)
Background and objectives: The prevalence of Helicobacter pylori infection differs in urban and rural population. In our country, no previous study investigated the H. pylori infection in rural population. The aim of the present study was to find out the status of H. pylori infection among the Bangladeshi asymptomatic rural adult population. Material and Methods: This cross-sectional study was carried out in a rural area located about 40 km north-east of capital Dhaka. Apparently healthy non-diabetic, pre-diabetic and diabetic adults (18 years and above) were enrolled in this study. A structured questionnaire was developed to record the socio-demographic and clinical information. H. pylori infection status was determined by the presence of anti- H. pylori IgG antibody in blood. Serum anti-H.pylori IgG antibodies were determined by immunochromatographic test (ICT) method. Results: A total number of 180 apparently healthy adult individuals were enrolled of which 112, 40 and 28 were non-diabetic, pre-diabetic and diabetic respectively. Out of 180 individuals, anti- H. pylori IgG was present in 70 (38.9%, CI: 32.1, 46.2) cases. Infection rate was 50%, 27.5% and 43.5% in 19-30, 31-50 and >50 years age group respectively. Infection rate was significantly (p< 0.05) low in 31-50 years age group compared to 19-30 and > 50 years age groups. H. pylori infection rates in male and female were 42.6% (CI: 29.2, 56.8) and 37.3% (CI: 28.9, 46.4) respectively (p=0.50). There was no significant (p>0.05) association of H. pylori infection with economic status, education level, occupation and tobacco consumption of the study population. The rate of H. pylori infection in non-diabetic, pre-diabetic and diabetic individuals were not significantly different from each other. Conclusion: The study revealed a low prevalence of H. pylori infection in rural population of Bangladesh. There was no significant association of H. pylori infection with several sociodemographic status and diabetes. Ibrahim Med. Coll. J. 2021; 15(1): 41-46